Hubungan Pengetahuan Dengan Perilaku Masyarakat Dalam Pencegahan Penularan Corona Virus Disease : Literature Review - Lisneni Dewi (Citra Delima Scientific journal of Citra Internasional Institute, 2023)
Coronavirus Disease (Covid-19) is a dangerous virus that infects the respiratory tract so that it can have an impact on death. The initial discovery of this virus came from China. The spread of the Covid-19 virus is very fast and the transmission rate is quite high. The rate of increase in cases is growing faster, so it takes people's behavior that can change themselves to maintain cleanliness. The public must also adhere to health protocols, such as wearing masks, washing hands and keeping a distance. The purpose of writing this literature review is to determine the relationship between knowledge and community behavior in preventing the transmission of COVID-19. This study uses the Literature Review method, namely by searching for article data sources taken using Google Scholar. The period of the articles that are used as references is from 2020 - 2021. From the results of the selection that has been carried out using the inclusion criteria, 10 articles are obtained that will be reviewed. The results obtained from the 10 articles reviewed were 6 articles which stated that there was a significant relationship between knowledge and community behavior in preventing Cofid-19. While the 3 articles there is no significant relationship.